2023
DOI: 10.3390/pharmaceutics15020436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dimerization, Dendrimerization, and Chirality in p-BthTX-I Peptide Analogs on the Antibacterial Activity and Enzymatic Inhibition of the SARS-CoV-2 PLpro Protein

Abstract: Recent studies have shown that the peptide [des-Cys11,Lys12,Lys13-(p-BthTX-I)2K] (p-Bth) is a p-BthTX-I analog that shows enhanced antimicrobial activity, stability and hemolytic activity, and is easy to obtain compared to the wild-type sequence. This molecule also inhibits SARS-CoV-2 viral infection in Vero cells, acting on SARS-CoV-2 PLpro enzymatic activity. Thus, the present study aimed to assess the effects of structural modifications to p-Bth, such as dimerization, dendrimerization and chirality, on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, this peptide demonstrated no toxicity against peritoneal macrophages. These findings align with those of Bitencourt et al, 42 who reported minimal hemolytic activity, below 5%, even at a 1 μM) than that of GVL1 alone. For the amastigote form, the IC 50 of (GVL1)-p-Bt was eight times lower than that of guanidine alone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, this peptide demonstrated no toxicity against peritoneal macrophages. These findings align with those of Bitencourt et al, 42 who reported minimal hemolytic activity, below 5%, even at a 1 μM) than that of GVL1 alone. For the amastigote form, the IC 50 of (GVL1)-p-Bt was eight times lower than that of guanidine alone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similarly, this peptide demonstrated no toxicity against peritoneal macrophages. These findings align with those of Bitencourt et al, who reported minimal hemolytic activity, below 5%, even at a concentration of 512 μg mL –1 , suggesting the nontoxic nature of p-Bt. The introduction of guanidine to p-Bt enhanced the antipromastigote activity of GVL1.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides exhibit characteristics that favor their use in therapeutic approaches, such as cellular biocompatibility and low toxicity [ 18 , 19 , 20 ]. The peptide (p-BthTX-I) 2 K is a synthetic peptide with a structure based on another peptide [(p-BthTX-I) 2 ] derived from the BthTX-I toxin in snake venom, which had previously demonstrated activity against several Gram-positive and Gram-negative bacteria [ 23 , 38 ] and antiviral activity against SARS-CoV-2 [ 24 ], which is an enveloped positive-sense single-stranded RNA virus similar to ZIKV and CHIKV. In this study, we assessed the antiviral activity of the (p-BthTX-I) 2 K peptide against CHIKV and ZIKV infection, as well as the steps in the viral replicative cycle in which this peptide shows activity.…”
Section: Discussionmentioning
confidence: 99%